2015
DOI: 10.5296/jas.v4i1.8790
|View full text |Cite
|
Sign up to set email alerts
|

Resource-Use Efficiency of Honey Production in Kachia Local Government Area, Kaduna-State, Nigeria

Abstract: This study examined resource-use efficiency of honey production in Kachia Local Government Area, Kaduna, Nigeria. The primary data used for the investigation were obtained using structured questionnaires administered to 50 producers. The data were analysed using descriptive statistics, farm budget techniques, multiple regression analysis and resource-use efficiency. Multiple regression analysis used to examine factors influencing output of honey in the study area revealed that the coefficient of multiple deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
2
0
0
Order By: Relevance
“…The more contacts a beekeeper has with extension services and the more beekeeping training they receive, the more economically efficient the beekeeper becomes. This finding is in line with that of Olohungbebe and Daniel (2015) who noted that adequate training on the rudiments of beekeeping determined the improvement of resource use efficiency for honey production in Nigeria. The training and extension services the beekeepers receive tends to strengthen beekeepers' technical know-how thereby improving their beekeeping performance.…”
Section: Determinants Of Farm-specific Economic Efficiencysupporting
confidence: 81%
“…The more contacts a beekeeper has with extension services and the more beekeeping training they receive, the more economically efficient the beekeeper becomes. This finding is in line with that of Olohungbebe and Daniel (2015) who noted that adequate training on the rudiments of beekeeping determined the improvement of resource use efficiency for honey production in Nigeria. The training and extension services the beekeepers receive tends to strengthen beekeepers' technical know-how thereby improving their beekeeping performance.…”
Section: Determinants Of Farm-specific Economic Efficiencysupporting
confidence: 81%
“…The proportion of MVP to MFC of the expenses on baiting materials was positive and smaller than one indicating the overuse of this resource. Here, labour used in honey production have a positive and significant relationship with the productivity which was also supported by Shrestha (2017) as well as (Dhakal et al, 2017) but Ahmad et al (2015) reported it as negative and insignificant. Migration cost had a positive and significant effect on productivity, which is supported by Paudel (2003), Dhakal et al (2017) as well as Shrestha (2017).…”
Section: Resource Use Efficiency Of Inputs Used In Beekeepingsupporting
confidence: 68%